The Effect of Participation in Regular Tennis Exercise on Sportsmanship - Hakan Eryiğit; Engin Efek (Türk Spor ve Egzersiz Dergisi)
This study examines the effect of participation in regular tennis exercise on sportsmanship in secondary school students. The research was carried out with an experimental method and sequential design. The study sample, 46 volunteer students, was divided into two groups as experimental and control groups. The “Personal Information Form” and the “Physical Education Lesson Sportsmanship Behavior Scale” were applied to the students in both groups as a pre-test in the first week and as a post-test after 12 weeks. Statistical Package for Social Sciences (SPSS) 17.0 program was used for data analysis. As a result of the normality tests (Skewness and Kurtosis), it was determined that the data showed normal distribution, so the Independent Sample T-Test and Paired Samples T-Test were applied. The significance level was accepted as p lt;0.05. According to the findings of the study, while there was a statistically significant difference between the pre-test (90.82 ± 14) and post-test (97.52 ± 10) of the experimental group's sportsmanship level, no statistically significant difference between the pre-test (85.73 ± 12) and post-test (83.52 ± 14) of the control group's sportsmanship levels between. Consequently, this study reveals that participation in 12 weeks of regular tennis exercise significantly increases the sportsmanship level of secondary school students.